Case report: Toxic epidermal necrolysis as a unique presentation of acute graft versus host disease in a pediatric patient - Marlowe, Elizabeth; Palmer, Rachel; Rahrig, April L.; Dinora, Devin; Harrison, Jessica; Skiles, Jodi; Rahim, Mahvish Q. (Frontiers in Immunology, 2025)
IntroductionAcute graft versus host disease (aGVHD) is a common complication of stem cell transplant (SCT), with skin involvement being most common. Severe presentations of skin aGVHD involving rapid progression of rash to bullae formation and mucosal involvement are rare. There are reports of patients with skin aGVHD that present with clinical characteristics mimicking toxic epidermal necrolysis (TEN), suggesting a possible overlap between the two. Management and outcomes of pediatric patients with this overlapping, severe presentation have rarely been described.Case presentationThis report describes an 11-year-old boy with refractory T-cell acute lymphoblastic leukemia who received peripheral blood SCT from a matched unrelated donor. Day 26 post-SCT, he developed a maculopapular facial rash, which progressed to the development of vesicles coalescing into bullae involving his conjunctiva, face, oral mucosa, and genital mucosa. Initially, systemic steroid monotherapy was initiated, but with rapid rash progression and mucosal involvement, intravenous immunoglobulin (IVIg) 2 g/kg divided over 5 days was added as management for suspected TEN-like aGVHD based on clinical findings. Ruxolitinib was subsequently started as adjunctive management for aGVHD. His skin findings continued to improve with near total resolution by day 49 post-SCT.ConclusionWe report a unique case of TEN-like aGVHD with rapid progression to >30% body surface area involvement including bullae formation and detachment of epidermis. There have been few case reports of similar presentations, most with poor outcomes. We aim to supplement the literature available by reporting our successful management with steroids, IVIg, and ruxolitinib, which resulted in early resolution of symptoms in a pediatric patient.